2019
DOI: 10.24953/turkjped.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the pediatric feeding and swallowing disorders family impact scale for Turkish children with cerebral palsy by endoscopic evaluation

Abstract: Öztürk EA. Reliability and validity of the pediatric feeding and swallowing disorders family impact scale for Turkish children with cerebral palsy by endoscopic evaluation. Turk J Pediatr 2019; 61: 741-748. The caregivers of children with cerebral palsy (CP) have high mood disorders and stress levels. This study was aimed to conduct validity and reliability of Turkish version of The Pediatric Feeding and Swallowing Disorders Family Impact Scale (PFSDFIS) by using an objective method. This study was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nine studies exclusively focused on infants under 1 year of age [ 12 20 ]; five samples consisted of children younger than 12 months up to 3 years [ 21 25 ]; one study focused on children between 4 and 8 years [ 26 ], and a wide age distribution including infants, children and adolescents could be found in seven studies [ 10 , 11 , 27 30 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies exclusively focused on infants under 1 year of age [ 12 20 ]; five samples consisted of children younger than 12 months up to 3 years [ 21 25 ]; one study focused on children between 4 and 8 years [ 26 ], and a wide age distribution including infants, children and adolescents could be found in seven studies [ 10 , 11 , 27 30 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of the samples showed that three studies included only infants from the neonatal intensive care unit (NICU) [ 12 , 14 , 18 ], one focused on mechanically ventilated children [ 23 ], and two had a surgical focus [ 13 , 25 ]. Six studies related to a single diagnosis or symptom: Congenital Zika Syndrome [ 22 ], isolated Pierre-Robin sequence [ 15 ], laryngomalacia [ 16 ] and gastroesophageal reflux disease (GERD) [ 17 ], cerebral palsy [ 26 ], and prematurity [ 19 ]. The remaining 10 samples varied widely in terms of principal diagnosis [ 10 , 11 , 20 , 21 , 24 , 27 31 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations